Composition adjustment of vacuum-arc Ti-Al-N films, deposited with use of two-channel filter - Aksyonov, D.S.; Aksenov, I.I.; Luchaninov, A.A.; Reshetnyak, E.N.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2011)
Composite films were formed by vacuum-arc method using two plasma sources equipped with aluminum and titanium cathodes. The sources were coupled with a dual channel T-shaped magnetic filter. Ability of Ti-Al-N films composition adjustment by deposition of mixed plasma streams from the plasma sources was investigated. It has been found that film composition can be varied by changing arc currents in plasma sources. However adjustment range of film composition is rather limited, and can be expanded by changing magnetic field intensity in anode area of plasma sources. Obtained films have uniform composition and thickness on 180 mm diameter surface. Conditions for aluminum content adjustment range from 14 to 60 wt.% were found.